Tetrahymena Comparative Genomics Database (TCGD): a community resource for Tetrahymena. (27th February 2019) - Yang, Wentao; Jiang, Chuanqi; Zhu, Ying; Chen, Kai; Wang, Guangying; Yuan, Dongxia; Miao, Wei; Xiong, Jie
Abstract: Ciliates are a large and diverse group of unicellular organisms characterized by having the following two distinct type of nuclei within a single cell: micronucleus (MIC) and macronucleus (MAC). Although the genomes of several ciliates in different groups have been sequenced, comparative genomics data for multiple species within a ciliate genus are not yet available. Here we collected the genome information and comparative genomics analysis results for 10 species in the Tetrahymena genus, including the previously sequenced model organism Tetrahymena thermophila and 9 newly sequenced species, and constructed a genus-level comparative analysis platform, the Tetrahymena Comparative Genomics Database (TCGD). Genome sequences, transcriptomic data, gene models, functional annotation, ortholog groups and synteny maps were built into this database and a user-friendly interface was developed for searching, visualizing and analyzing these data. In summary, the TCGD (http://ciliate.ihb.ac.cn ) will be an important and useful resource for the ciliate research community.